Copper and cobalt nanoparticles containing poly(acrylic acid‐co‐acrylamide) hydrogel composites for rapid reduction of 4‐nitrophenol and fast removal of malachite green from aqueous medium. Issue 9 (5th March 2017) - Naseer, Fehmida; Ajmal, Muhammad; Bibi, Fouzia; Farooqi, Zahoor H.; Siddiq, Muhammad
Abstract : Poly(acrylic acid‐co‐acrylamide) (p(AAc‐co‐AAm)) hydrogels were synthesized and used as templates for the synthesis of metal nanoparticles. Metal nanoparticles were prepared by in situ reduction of Cu(II) and Co(II) ions. The metal nanoparticles inside the hydrogel were visualized by transmission electron microscope (TEM). Thermal properties of the bare hydrogel and hydrogel composites were investigated by differential scanning calorimeter (DSC) and thermal gravimetric analysis (TGA). The prepared p(AAc‐co‐AAm)‐M (M = Co and Cu) composites were used as catalysts for the reduction of 4‐nitrophenol (4‐NP) and as adsorbent for the removal of malachite green (MG) from aqueous medium. The effects of temperature and the amount of catalyst were also investigated on the reduction of 4‐NP and various thermodynamic parameters such as activation enthalpy (Δ H # ), activation entropy (Δ S # ), and activation Gibb's energy (Δ G # ) were calculated. The reusability of the composites up to four consecutive cycles was also investigated. Additionally, the effect of amount of adsorbent and concentration of adsorbate (MG) on the adsorption of MG was studied. Langmuir, Freundlich, and Temkin adsorption isotherms were applied and adsorption kinetic parameters were calculated. The adsorption kinetics was also studied, and it was found that adsorption of MG by p(AAc‐co‐AAm) hydrogel followed the pseudo second‐order kinetics. POLYM. COMPOS., 39:3187–3198, 2018. © 2017 Society of Plastics Engineers